Nano-Crystalline Cellulose as a Novel Tablet Excipient for Improving Solubility and Dissolution of Meloxicam - Laila H. Emaraa, Ahmed A. El-Ashmawya, Nesrin F. Tahaa, Khaled A. El-Shaffeib, El-Sayed M. Mahdeyb, Heba K. Elkhollyc (Journal of Applied Pharmaceutical Science, 2016)
This study explored the effect of nano-crystalline cellulose (NCC) on Meloxicam (MX) solid dispersion (SD) prepared by co-grinding technique compared to micro-crystalline cellulose (MCC) in presence of lactose. MX-tablets were prepared by direct compression of different co-ground SDs or physical mixtures. The solubility, dissolution, SEM and DSC of different preparations were studied. Flow-through cell apparatus (FTC) was used to study the dissolution of MX from tablets at pH 7.4. Generally, the results revealed that increasing NCC loadings showed a direct increase in both the solubility and dissolution of MX. MCC did not improve either the solubility or the dissolution of MX in the physical mixture, while, co-grinding dramatically decreased the dissolution rate of MX. It was interesting to find that grinding of MX-powder alone or in a mixture with lactose highly increased MX solubility and dissolution. SEM as well as DSC were found to be very good tools, without a single exception, to describe the observed solubility and dissolution of MX in these proposed preparations. SEM-images showed the particle size reduction upon grinding or co-grinding techniques. While DSC-data proved that the crystalline structure of MX has been changed to an amorphous state.
Keywords: Co-grinding solid dispersion, flow-through cell apparatus, water insoluble drug, micro-crystalline cellulose, scanning electron microscope, differential scanning calorimetry.